A cost-effectiveness analysis for high versus standard (low) dose caffeine for the treatment of apnea in neonatal intensive care unit - Eilan Al-Hersh; Dina Abushanab; Fouad AbouNahia; Daniel Rainkie; Moza Al Hail; Palli Valapila Abdulrouf; Wessam El-Kassem; Daoud Al-Badriyeh (Taylor & Francis Group, 2024)
ABSTRACTObjective: Preterm babies are prone to experiencing apnea of prematurity (AOP), mostly characterised by a pause in breathing lasting a minimum of 20 seconds. Recent literature supported higher maintenance doses of caffeine, indicating benefits. This study evaluated the cost-effectiveness of high maintenance dose (HD) versus low maintenance dose (LD) caffeine for AOP in neonates.Methods: From the hospital perspective of Hamad Medical Corporation (HMC), Qatar, a cost-effectiveness decision-analytic model was constructed to follow the use of a HD maintenance caffeine of 20 mg/kg/dose versus a LD maintenance caffeine of 10 mg/kg/dose, in a simulated cohort of AOP neonates, over a therapy follow-up duration of six weeks, until neonatal intensive care (NICU) discharge. The clinical inputs were primarily literature-based, while the resource cost and utilisation were locally extracted in HMC. The cost-effectiveness outcome measure was calculated per therapy success, defined as survival with no apnea and successful extubation removal within 72 hours, with or without adverse events. One-way and multivariate sensitivity analyses were performed to confirm the robustness of the results.Results: With 0.23 (95% CI, 0.23-0.23) enhancement in success rate, at United States dollar (US$) 3869 (95% CI, US$ 3823-3915) added infant cost, the HD caffeine was between dominant (34.8%) and cost-effective (63.7%), with an average incremental cost-effectiveness ratio of US $16,895 (95% CI, US$ 15,242-18,549) relative to LD caffeine per additional case of success. The hospitalisation contributed the most to the total infant cost, and the probability of patent ductus arteriosus was the model input that influenced the results most.Conclusion: This is the first literature economic evaluation of caffeine for AOP. Despite increasing the cost of therapy, HD maintenance caffeine seems to be a cost-effective alternative to LD caffeine in Qatar. Our results support the recent global trends of increased use of HD caffeine for AOP in NICU.